Whether groups value agreement or dissent depends on the strength of consensus - James C. Mellody (PLoS ONE, 2025)
I investigate the conditions under which groups value agreement versus dissent in collective decision-making processes. I argue that which kind of contribution a group values more will depend on the strength of the consensus. As a consensus evolves from weak to moderate to strong, I predict that groups will prefer agreement, dissent, and then agreement again. These predictions are in line with a multi-phase decision-making process in which groups pursue sequential goals reflected in the evolving consensus: establishing an initial consensus, exploring alternative perspectives, and settling on a final decision. I test these predictions with data from the Reddit community r/AmItheAsshole, in which people make normative judgments of social situations. I find support for the predicted pattern, with one caveat: when the consensus is strong, groups exhibit no preference for agreement or dissent.